2016
DOI: 10.1080/09583157.2016.1205181
|View full text |Cite
|
Sign up to set email alerts
|

Induction of defence-related enzymes in tomato (Solanum lycopersicum) plants treated with Bacillus subtilis CBR05 against Xanthomonas campestris pv. vesicatoria

Abstract: Induction of defense-related enzymes in tomato (Solanum lycopersicum) plants treatedwith Bacillus subtilis CBR05 against Xanthomonas campestris pv. vesicatoria Running Head: B. subtilis CBR05 induced defense-related enzymes in tomato ABSTRACT Bacterial spot disease, caused by Xanthomonas campestris pv. vesicatoria is one of the most important destructive diseases of tomato in many parts of the agricultural world. Bacillus sp.has been reported to be significantly reducing the incidence of disease in the diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Similarly, increases in total flavonoids content by B. licheniformis have been reported for tomato fruits [32]. In our previous studies, we also found that B. subtilis CBR05 inoculation enhanced the accumulation of peroxidase and polyphenol oxidase enzymes, which are involved in the metabolism of phenols and flavonoids [22,23]. Hence, this shows that B. subtilis colonization induces resistance against biotic and abiotic stress agents.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similarly, increases in total flavonoids content by B. licheniformis have been reported for tomato fruits [32]. In our previous studies, we also found that B. subtilis CBR05 inoculation enhanced the accumulation of peroxidase and polyphenol oxidase enzymes, which are involved in the metabolism of phenols and flavonoids [22,23]. Hence, this shows that B. subtilis colonization induces resistance against biotic and abiotic stress agents.…”
Section: Discussionsupporting
confidence: 76%
“…The use of PGPR is increasing in agriculture and may offer an attractive alternative to synthetic chemicals and fertilizers. Plant growth-promoting microorganisms are efficient microbial competitors that can promote plant growth by producing phytohormones and/or by increasing available nutrients through production of secondary metabolites or act as biocontrol agents to protect plants from infection by phytopathogens [19,[21][22][23][24]. There have been many reports on PGPR and their effective roles [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased peroxidase activity is also well observed in rhizobacteria-induced systemic resistance. Chandrasekaran and Chun (2016) demonstrated that treating tomato plants with Bacillus subtilis CBR05 significantly enhanced the activities of antioxidant enzymes including peroxidase. Yanti (2015) reported that rhizobacteria enhanced peroxidase enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…A numerous study indicated that ISR can be trigged through several compounds produced by endophytes such as phytohormones, lipopeptides, pyocyanin, siderophore, and VOCs [135][136][137][138]. ISR triggered by endophytic bacteria can protect the host against a wide range of pathogens including soilborne pathogenic fungi [139][140][141], biotrophic pathogens [142,143], viruses [144][145][146], nematodes [147], and insect herbivores [148,149].…”
Section: Indirect Interactions In the Holobiontmentioning
confidence: 99%